Developing Researcherhood: Identity Tensions and Identity Work of Women Academics Reflecting on Their Researcher Identity - Helene Antoni Barnard (Forum: Qualitative Social Research, 2019)
In this article, I explore the researcher identity of senior women academics in a South African institution of higher education. The aim was to uncover the identity tensions they experience in relation to being a researcher and to understand how they respond to and resolve these tensions. Three focus groups, based on the socioanalytic method of social dream drawing, provided the data. Data were analyzed through hermeneutic phenomenological reflection. Identity theory was applied as a conceptual framework to guide my interpretation of the data. Through their collective reflection on being researchers, the women became cognizant of identity tensions and their engagement with these reflected intrapersonal processing akin to identity work. In the findings, I highlight purposeful, collective identity work as a resource that enabled these women to re-construct self-defeating gendered conflicts in their researcherhood. By uncovering their identity tensions and related emotions, a sense of researcher self-efficacy emerged. They consequently reframed research success as meaningful self-expression and knowledge dissemination. I propose that collective identity work is a valuable endeavor for women researchers because it facilitates role identity development and a collective voice in responding to the demanding and constantly changing academic work context.